Bridging the innovation system and industry development: experiments from Northern Finland. (2nd September 2020) - Longi, Henna; Niemelä, Sami; Leppänen, Tero
As technological change has been identified as a one important driver of economic growth, the interest towards research, development, and innovation (RDI) has increased in academia and also in policy practices. However, a systemic analysis of innovation activities easily overlooks the role of the companies as key actors building the bridge between innovations and economic growth. Combining the analyses of innovation systems and entrepreneurial activities is important in ensuring the recognition of public and private stakeholders in regional development. This paper discusses the interplay of public and private sectors and concentrates on the companies and industry development in innovation systems. The case study in this article comes from the Oulu region in Northern Finland. This paper aims at describing and analysing public-funded projects as links between RDI and business development.